2021
DOI: 10.1080/09638288.2021.1971306
|View full text |Cite
|
Sign up to set email alerts
|

Orthotic Research Initiative for Outcomes aNalysis (ORION I): predictors of PROMIS PF for stroke survivors seeking orthotic intervention

Abstract: Purpose: Ankle-foot orthoses (AFOs) are used to improve physical performance measures of physical function (PF) post-stroke; however, the perception of improved PF of this population has not been described. The purpose of this study was to identify the predictors of self-reported PF of individuals seeking orthotic intervention post-stroke. Materials and Methods: A retrospective analysis of 237 patients at a nationwide orthotic services provider in the United States was conducted to characterize PF using the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…PROMIS-PF scores are centered on responses from a general population and may be challenging to interpret when assessing mobility of LLO users. DiBello et al reported that people who received an AFO post-stroke had a mean PROMIS-PF T-score of 30.8—nearly two standard deviations below the general population mean [ 11 ]. It is challenging to accurately measure and evaluate changes in mobility with PROMIS-PF when LLO users are so near the floor of the scale (i.e., a T-score of 30.8 places someone within the bottom 3% of the US general population).…”
Section: Introductionmentioning
confidence: 99%
“…PROMIS-PF scores are centered on responses from a general population and may be challenging to interpret when assessing mobility of LLO users. DiBello et al reported that people who received an AFO post-stroke had a mean PROMIS-PF T-score of 30.8—nearly two standard deviations below the general population mean [ 11 ]. It is challenging to accurately measure and evaluate changes in mobility with PROMIS-PF when LLO users are so near the floor of the scale (i.e., a T-score of 30.8 places someone within the bottom 3% of the US general population).…”
Section: Introductionmentioning
confidence: 99%
“…Another study used PROMIS-PF to assess 237 AFO users affected by stroke and reported a mean T-score that was two standard deviations below the U.S. general population. 30 Although these studies illustrate potential applications for PROMIS-PF in LLO-related research, the general population-based scoring system may limit its utility as a clinical assessment tool. Thus, although LEFS, OPUS-LEFS, and PROMIS-PF may be applicable to LLO users, their clinical utility may be limited by a general population focus and/or forms that do not allow for customization to specific types of users.…”
Section: Introductionmentioning
confidence: 99%
“…Weber et al 29 tested PROMIS‐PF in a sample of 98 LLO users and reported initial evidence of known groups construct validity. Another study used PROMIS‐PF to assess 237 AFO users affected by stroke and reported a mean T‐score that was two standard deviations below the U.S. general population 30 . Although these studies illustrate potential applications for PROMIS‐PF in LLO‐related research, the general population‐based scoring system may limit its utility as a clinical assessment tool.…”
Section: Introductionmentioning
confidence: 99%